Preclinical evaluation of reversible pulsed electrical field: electrophysiological and histological assessment of myocardium - Zhai, Zongwang; Ling, Yuchen; Wang, Yanjiang; Shi, Liang; Liu, Xingpeng (Frontiers in Cardiovascular Medicine, 2024)
Background Pulsed field ablation, as a non-thermal ablation modality, has received increasing attention. The aim of this study is to explore whether a reversible pulsed electric field (RPEF) can temporarily inhibit electrical conduction and provide a novel method for precise ablation of arrhythmia. Methods RPEF energy was delivered from an ablation catheter to the atrium of six dogs, followed by a series of electrogram and histology assessments. Results RPEF ablation of ordinary myocardium resulted in an average reduction of 68.3% (range, 53.7%–83.8%) in electrogram amplitude, while 5 min later, the amplitude in eight electrograms returned to 77.9% (range, 72.4%–87.3%) of baseline. Similarly, the amplitude of the sinoatrial node electrograms reduced by an average of 73.0% (range, 60.2%–84.4%) after RPEF ablation, but recovered to 84.9% (range, 80.3%–88.5%) of baseline by 5 min. No necrotic change was detected in histopathology. Transient third-degree atrioventricular block occurred following the ablation of the maximum His potential sites with RPEF, the duration of which was voltage dependent. The histopathological results showed necrosis of the myocardium at the ablation sites but no injury to His bundle cells. Conclusions RPEF can be applied to transiently block electrical conduction in myocardial tissues contributing to precise ablation.